Fluoroquinolones and Other Antibiotics Redeemed for Cystitis-A Swedish Nationwide Cohort Follow-Up Study (2006-2018) - Xinjun Li; Kristina Sundquist; Filip Jansåker (MDPI AG, 2022)
Background: Antibiotics are commonly prescribed for outpatient management of cystitis. Previous evidence suggests that certain factors likely beyond the infection seem to influence the choice of antimicrobial treatment. However, studies on the specific antibiotic treatments for cystitis are lacking. This study aimed to explore the antibiotic treatments for cystitis using nationwide primary healthcare data and investigate if factors beyond the infection could be associated with fluoroquinolone treatment. Methods: This nationwide follow-up cohort study consisted of 352,507 women with cystitis. The primary aim was to investigate what specific classes of antibiotics were redeemed by patients within five days from the cystitis diagnosis. Each patient could only be included once. Logistic regression models were also used to examine the relationship between fluoroquinolone (FQ) treatment, parity, and sociodemographic factors. Results: In total, 192,065 antibiotic prescriptions were redeemed. Pivmecillinam (58.4%) followed by nitrofurantoin (22.2%), trimethoprim (12.0%), fluoroquinolone (5.6%), and cephalosporins (1.5%) were the most redeemed antibiotics. Sociodemographic factors were weakly associated with fluoroquinolone treatment; young age was inversely associated with fluoroquinolone treatment. Parity and cervical cancer history were not associated with fluoroquinolone treatment. The proportion of fluoroquinolone and trimethoprim treatments decreased over time, while pivmecillinam and nitrofurantoin increased. Conclusions: The treatment trends of antibiotics redeemed within five days from a cystitis diagnosis were similar to the national surveillance program of these antibiotics (not diagnosis linked). Fluoroquinolones were weakly associated with sociodemographic factors, which likely is only of historical relevance.